Measuring cornea - Oliveira, Cristina M. (2012)
By virtue of its remarkable mechanical strength and optical transparency, the cornea serves as the major refractive element of the eye while protecting its contents. These properties are directly attributable to the cornea's structural architecture of collagen fibrils and surrounding hydrated matrix containing proteoglycans, glycoproteins, other soluble proteins, inorganic salts and keratocytes. [1,2] The maintenance of corneal shape and transparency is crucial for its optical function. The optical properties of the cornea are mainly governed by its collagen fibril organization, which ensures that the cornea maintains correct surface shape under the action of intraocular pressure on its internal surface.[3]